Defect and Distortion in Powder Bed Fusion of Metal Additive Manufacturing Parts - Ajay Kumar Maurya; Amit Kumar (Universitas Gadjah Mada, 2022)
One of the state-of-the-art technologies for metal fabrication is laser powder bed fusion, which includes the following printing techniques: selective laser melting, selective laser sintering, direct metal laser sintering, and electron beam melting. This work examines defect formation in laser powder bed fusion, predominately focusing on selective laser melting. It also explores recent research findings on defect formation and classification and analyzes various internal defects, such as porosity, lack of fusion, balling, and solidification cracking. The influence of process parameters on defect formation and the effect of defects on mechanical properties are analyzed. This review also discusses defect inspection technologies (melt pool, scan path, and slice monitoring), defect mitigation strategies (online detection, process parameters, and numerical simulation), and their applications in additive manufacturing, such as laser powder bed fusion. This review would aid manufacturers in determining the root cause of defect formation and developing inspection technologies and mitigation strategies.